Teaching Gen-Z at SMP N Langga Payung, Indonesia: What are the Teachers’ Preferences of Using Media in Their English Language Teaching? - Siregar, Sri Rahmadhani; Eka Sustri Harida; Puspita Amelia (ELITE JOURNAL, 2025)
The students of Gen-Z have a preference to study with their gadgets then with their teachers; it raises some challenges for the teacher. Language teaching media is very helpful to give the solutions. This study explores the teachers’ preferences to use media in teaching the Gen-Z students at SMPN 1 Langga Payung, North Sumatera, Indonesia, in English language teaching. It is explored with a descriptive qualitative method; data were accumulated from English teachers and students through observations and interviews, and analyzed qualitatively with data reduction, data display, and conclusion drawing. Two primary factors were found in this study: 1) the media used and 2) the challenges. The results show that teachers used audio media (songs, YouTube), visual media (textbooks, PowerPoint), and audio-visual media (videos, Word wall) to make it suitable to the Gen Z learning styles; and the students showed interest and highly motivated. However, the challenges came, such as poor internet access, limited digital skills, and students’ distractions. The study concludes that teachers should use appropriate media to support effective and interactive English teaching and learning for Gen Z students. The media used in English language teaching can be more variative and selective; and it needs further study to explore more, especially the digital media or tools that can be used appropriately to the students in rural areas of study.